Slurry sample injection for determination of ferrite nanocolloids chemical composition by ICP spectrometry - Sousa, M. H.; Lins, E. S.; Tourinho, F. A.; Depeyrot, J.; De Castro, G. R. [UNESP]; Martins, W. D.; Castro, C. F S; Zara, L. F. (My University, 2007)
This work proposes a new method to determine the chemical composition of magnetic ferrite nanoparticles by the slurry injection technique using the inductively coupled plasma optical emission spectroscopy. In this way, experimental conditions such as aerosol gas flow rate and colloidal stability were optimized in order to use aqueous calibration curves in the slurry nebulization and to determine the chemical composition of a series of sols containing chemically synthesized size-tailored NiFe 2O 4 nanograms. Then, the results of direct sampling and those of conventional aqueous introduction analysis are compared, showing the efficiency of the proposed method.
Keywords: Ferrite nanoparticle; Icp-oes; Magnetic colloid; Slurry injection; Colloids; Ferrites; Flow of gases; Magnetic materials; Nanoparticles; Ferrite nanoparticles; Magnetic colloids; Slurries